Optical spectroscopy and current detection during warm-up and destruction of impurity-helium condensates - Krushinskaya, I. N.; Bykhalo, I. B.; Boltnev, R. E.; Pelmenev, A. A.; Khmelenko, V. V.; Lee, D. M. (Хабаршы. Физика сериясы, 2015)
It is well known that deposition of rare gases (RG) passed through electrical discharge area onto a cold ( 4 K) surface, or irradiation of cryofilms by energetic particles (electrons, protons, or photons with energies of 20 eV – 4 MeV) can cause formation and stabilization of neutral radicals and ions. Recent experiments have revealed ion currents accompanied by luminescence during destruction of nitrogenhelium condensates prepared by condensation of nitrogen-helium gas mixtures (after passing through a radio frequency RF discharge zone) into superfluid helium (HeII) bulk [1].